Para-Toluenesulfonamide Induces Anti-tumor Activity Through Akt-Dependent and -Independent mTOR/p70S6K Pathway: Roles of Lipid Raft and Cholesterol Contents - Hsu, Jui-Ling; Leu, Wohn-Jenn; Hsu, Lih-Ching; Liu, Shih-Ping; Zhong, Nan-Shan; Guh, Jih-Hwa (Frontiers in Pharmacology, 2018)
Castration-resistant prostate cancer (CRPC) cells can resist many cellular stresses to ensure survival. There is an unmet medical need to fight against the multiple adaptive mechanisms in cells to achieve optimal treatment in patients. Para-toluenesulfonamide (PTS) is a small molecule that inhibited cell proliferation of PC-3 and DU-145, two CRPC cell lines, through p21- and p27-independent G1 arrest of cell cycle in which cyclin D1 was down-regulated and Rb phosphorylation was inhibited. PTS also induced a significant loss of mitochondrial membrane potential that was attributed to up-regulation of both Bak and PUMA, two pro-apoptotic Bcl-2 family members, leading to apoptosis. PTS inhibited the phosphorylation of m-TOR, 4E-BP1 and p70S6K in both cell lines. Overexpression of constitutively active Akt rescued the inhibition of mTOR/p70S6K signaling in PC-3 cells indicating an Akt-dependent pathway. In contrast, Akt-independent effect was observed in DU-145 cells. Lipid rafts serve as functional platforms for multiple cellular signaling and trafficking processes. Both cell lines expressed raft-associated Akt, mTOR and p70S6K. PTS induced decreases of expressions in both raft-associated total and phosphorylated forms of these kinases. PTS-induced inhibitory effects were rescued by supplement of cholesterol, an essential constituent in lipid raft, indicating a key role of cholesterol contents. Moreover, the tumor xenograft model showed that PTS inhibited tumor growth with a T/C (treatment/control) of 0.44 and a 56% inhibition of growth rate indicating the in vivo efficacy. In conclusion, the data suggest that PTS is an effective anti-tumor agent with in vitro and in vivo efficacies through inhibition of both Akt-dependent and -independent mTOR/p70S6K pathways. Moreover, disturbance of lipid raft and cholesterol contents may at least partly explain PTS-mediated anti-tumor mechanism.